Cyber Battle Management Systems (CBMS) is Considered as Systems of Systems (SoS) and Emergent Behavior is Present, where Viable System Model (VSM) only Controls System Variety - Aleksandar Seizovic; Steven Goh; David Thorpe; Lucas Skoufa (Applied Artificial Intelligence)
This manuscript critically examines existing research on cyber battle management systems (CBMS) and underscores the importance of advancing complex structure thinking, cybernetics, wicked problem-solving, and emerging behavior analysis. It advocates for a systems-thinking approach to solving complex problems by identifying and understanding associated systems, predicting their behavior, and managing changes. The manuscript explores the integration of cybernetics meta-methodology and the viable system model with metasystems reductionism to address negative emergent behavior in complex systems. The study highlights the roles of individual systems, systems of systems, and metasystems, emphasizing the deterministic nature of single systems and the stochastic characteristics of systems of systems. By integrating cybernetics, viable system models, and meta-metasystems, the manuscript explores key parameters for building intelligent systems, revealing that meta-metasystems offer superior capabilities for coordinating and integrating multiple systems. The research results demonstrate the successful development of a meta-metasystem tailored for CBMS, providing a strategic framework for the future of cyber battle management.